2018
DOI: 10.1159/000493103
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thinning Associated with Age and CSF Biomarkers in Early Parkinson’s Disease Is Modified by the SNCA rs356181 Polymorphism

Abstract: The role of cerebrospinal fluid (CSF) biomarkers such as CSF α-synuclein and CSF tau in predicting cognitive decline in Parkinson’s disease (PD) continues to be inconsistent. Here, using a cohort of de novo PD patients with preserved cognition from the Parkinson’s Progression Markers Initiative (PPMI), we show that the SNCA rs356181 single nucleotide polymorphism (SNP) modulates the effect of these CSF biomarkers on cortical thinning. Depending on this SNP’s genotype, cortical atrophy was associated with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…c The criteria by which PD was diagnosed. Where “mixed” is indicated for multicenter studies, GEO-PD (included in Chung et al 21 , Elbaz et al 76 , and Maraganore et al 15 ) used UKBB, Gelb, Bower, the Core Assessment Program for Intracerebral Transplantations (CAPIT) and criteria described in Pals et al 81 and PPMI (included in Bjørnarå et al 47 , Sampedro et al 67 , and Caspell-Garcia et al 68 ) used criteria outlined in the study protocol ( http://www.ppmi-info.org ; Parkinson Progression Marker Initiative 82 ). d The number of patients with PD included in the whole study cohort.…”
Section: Resultsmentioning
confidence: 99%
“…c The criteria by which PD was diagnosed. Where “mixed” is indicated for multicenter studies, GEO-PD (included in Chung et al 21 , Elbaz et al 76 , and Maraganore et al 15 ) used UKBB, Gelb, Bower, the Core Assessment Program for Intracerebral Transplantations (CAPIT) and criteria described in Pals et al 81 and PPMI (included in Bjørnarå et al 47 , Sampedro et al 67 , and Caspell-Garcia et al 68 ) used criteria outlined in the study protocol ( http://www.ppmi-info.org ; Parkinson Progression Marker Initiative 82 ). d The number of patients with PD included in the whole study cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that telomere length may influence the occurrence of dementia in PD patients [ 22 ]. Additionally, several studies have argued for the existence of genetic modifiers of PD clinical presentation, such as TMEM106B [ 23 ], SCNA [ 24 ], and COMT [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variables included individual APOE genotype, MAPT haplotype and the SNPs rs12411216 38 , rs356181 39 and rs3910105 40 . GBA mutation status was included as a binary factor for the presence of any non-synonymous coding mutations present within the GBA region.…”
Section: Methodsmentioning
confidence: 99%